1999
DOI: 10.1046/j.1365-2419.1999.00020.x
|View full text |Cite
|
Sign up to set email alerts
|

Exchange and flux of larval fishes across the western Gulf Stream front south of Cape Hatteras, USA, in winter

Abstract: To describe exchange and to frame the magnitude of the flux of larval fishes across the Gulf Stream front in winter, collections were taken on the inshore and offshore sides of the frontal zone in 1991, 1993, 1994 and 1995, off Onslow Bay, North Carolina. Collections yielded larval fishes representing 75 families. Of these, the larvae of the families Gonostomatidae or Phosichthyidae consistently occurred on both sides of the frontal zone, yet are exclusively of mesopelagic, deep‐oceanic origin; hence, they ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 36 publications
(57 reference statements)
2
24
0
Order By: Relevance
“…In view of the importance of frontal processes to nutrient distribution and biological productivity in the East China Sea (Liu et al 1992) and other frontal systems (e.g., Govoni and Spach 1999;Mauna et al 2008), this work continues that of Chang et al (2010) to better understand the physics of windinduced frontal circulation. Cross-frontal circulation and mixing processes inferred from a set of high-resolution numerical experiments (0.25 km horizontal grid and 0 (1 m) vertical grid) are studied.…”
Section: Introductionsupporting
confidence: 55%
“…In view of the importance of frontal processes to nutrient distribution and biological productivity in the East China Sea (Liu et al 1992) and other frontal systems (e.g., Govoni and Spach 1999;Mauna et al 2008), this work continues that of Chang et al (2010) to better understand the physics of windinduced frontal circulation. Cross-frontal circulation and mixing processes inferred from a set of high-resolution numerical experiments (0.25 km horizontal grid and 0 (1 m) vertical grid) are studied.…”
Section: Introductionsupporting
confidence: 55%
“…Larval fishes, however, need more light to capture prey and are commonly present near the surface during the day. Govoni & Spach (1999) found that the total larval fish abundance in the same 1991 trawl samples that are used here to report Anomalocera ornata numbers, was low (< 0.13 larvae m -3 at 12:00 h above 20 m). Their data indicated that larvae were most abundant around 20 m at night (<1.0 larvae m -3 ), not at the surface during the day.…”
Section: Discussionmentioning
confidence: 66%
“…The sam- pling design used during the cruises was optimized to examine the flux of winter-spawned larval fishes across the western Gulf Stream front south of Cape Hatteras, USA (see Govoni & Spach 1999). However, because dense surface patches of large blue copepods, identified as Anomalocera ornata, were noted during these winter cruises, the copepods were sorted from the cruise samples after the larval fishes had been removed.…”
Section: Methodsmentioning
confidence: 99%
“…Blanton and Pietrafesa (1978) estimated a complete flushing time of Onslow Bay of 60 d, with bottom waters moving in and surface waters leaving. Govoni and Spach (1999) and Grothues and Cowen (1999) estimated large fluxes of larvae off the SEUSCS. Future work should attempt to quantify loss relative to recruitment of species that spawn on the SEUSCS and depend on SEUSCS nursery habitats.…”
Section: Discussionmentioning
confidence: 99%